Venezuela: Potential demand for cassava - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Price, credit, and government spending policies and their impact on agriculture in Venezuela are analyzed. The status of demand for fresh cassava is reviewed as well as the potential demand for both fresh and dried cassava. Cassava has much to offer as the cheapest source of energy in the tropics; yet the crop is out of the mainstream of government import substitution and agroindustrial policies, which are influenced by food processers who import their own raw materials. Production has stagnated with yields of 8 t/ha on 40,000 ha. Given its adaptation to different environments, cassava is an excellent candidate, in the long term, to substitute imported food/feed energy sources. The current dilemma of substituting expensive local grains for cheap imported ones while trying to provide cheap, abundant food to the urban consumer must be broken by means of productivity, rather than area expansion, so prices of local products can be kept low and competitive. There are good prospects for both fresh and dried cassava. The new CIAT storage technology will enable farmers from distant places to enter the market, while retailers will have fewer losses and will also be able to negotiate larger volumes at wholesale outlets. (CIAT)